Delawar Qaradaghy’s Poems in the lights of picture’s - Hussein Ghazi Kak Amin (Zanco Journal of Humanity Sciences)
Actually, modern Kurdish poets have a high educational level, they lived in the reality of their nations and they faced many calamities and catastrophes as their nation. They perceived all the miserable conditions and genocide confronted Kurdish people. This has been an observable factor in their modern poetry, and they have also been aware of all the changes happened in the field of poetry in the outside world. This has given a beautiful poetic image to the structure of Kurdish poetry. That is why the readers have highly appreciated their poetry. The Kurdish poets, especially Qaradaxy, could gather various types of poetic images in his poetry, such as single, compound, general, stable, mobile images as well as the images perceived by the five senses (sight, tasting, hearing, smelling, and touching). By manipulating these nice images, this poet could make a beautiful realistic image to attract the readers’ attention. Another feature of their poetry was that they didn’t look at nature as it is, but as human which has been widely used in their poetry.